Peran Esensial Keluarga Penderita Hipertensi - Ulfah Agus Sukrillah; Herry Prasetyo; Walin Walin (Prodi Keperawatan Purwokerto, 2021)
Background: Hypertension disease still occupies the largest proportion of infectious diseases carried out as much as 64.83% while the second most is diabetes mellitus by 19.2%. Both diseases are the top priorities for non-communicable disease control in Indonesia and the world. Please be aware that the family relationship of the closest person such as family is a good support for people with any disease as well as hypertension disease.Methods: The subject of the study is people with hypertension. Type of journal that is original article instead of review of research theme of family support journal content in people with hypertension Type of research that is quantitative data collection of article selection process is determined in accordance with inclusion criteria. The data collection process uses the extraction method.The Result: the prevalence of hypertension that occurs more in women after the age of 45 to 55 years is due to the production of estrogen hormones that gradually decrease naturally with age. The level of education of respondents is known to be mostly basic education.Conclusion: firstly the characteristics of the elderly mostly have the age of the elderly category have a female gender and have a basic education. The second one treats patients modifying the environment and utilizing health facilities positive effects of family support for people with hypertension.